ORIENTATION DEPENDENCE OF LUMINESCENCE IN PLAGIOCLASE - Finch A.A.; Hole D.E.; Townsend P.D. (My University, 2003)
The orientation dependence of the luminescence of a well-characterized plagioclase crystal at room temperature and 40 K is reported. A beam of H+ ions was used to provide the excitation. Ion beam luminescence provides emissions effectively from the bulk of the material, and therefore minimizes the contribution to the luminescence from atypical regions. The intensity of the luminescence is strongly orientation-dependent. The intensity and photon energy, particularly of the red/infrared and yellow emission bands, vary significantly. We interpreted this as resulting from Fe3+ and Mn2+ activator ions, respectively, on crystallographic sites with low point symmetry. An emission at 860 nm was also significantly orientation-dependent. The blue luminescence showed the least variability. At room temperature, a 350 nm near-UV emission was noted, whereas at 40 K, emissions were at 240, 260, 300 and 340 nm. UV emissions may result from Na+ diffusion along interfaces within the plagioclase, notably albite-law (010) twins. This variability has significant consequences for the use of single-crystal quantitative luminescence techniques. We have also studied the dependence of the peak intensities and profiles during prolonged ion beam bombardment with heavier (He+) ions. Broadening of the red-infrared emission is interpreted as reflecting growing amorphization of the sample.
Keywords: FELDSPAR; IONOLUMINESCENCE; ION BEAM LUMINESCENCE